Nautical Ad-hoc Network Application Development for Maritime Communications - Capt. Samson Joseph (Institute of Advanced Engineering and Science, 2017)
High data rate communication in terrestrial wireless scenarios can be accomplished by setting up Base Stations (BS) on the ground. But applying the similar technique to maritime communication may not be suitable because owing to the geographically constrained nature of the ocean, henceforth, MF/HF modems, extensive-distance transmission characteristics with low data-rate are commonly employed in maritime communiqué. Inmarsat is conservatively used in Maritime satellite communiqué in order to reimburse for low data-rate transmission of MF/HF modems, but its main negative aspect is high cost. To improve the transmission speed along with low price, in general, a network whose architecture is similar to Vehicular Adhoc Network (VANET), that permits peer-to-peer transportation without BS, i.e., ad-hoc network is critical. An ad-hoc network for nautical environment named as Nautical Ad-hoc Network (NANET) was proposed. Multiple access and duplexing schemes are used to implement the nautical network for corresponding NANET scenarios.